Daily Competency Notes as a Strategy to Observe the Development of Clinical Competence of NICU Nurses at Hospital X - Ratna Meilina; Tuti Afriani; La Ode Abdul Rahman; Rr Tutik Sri Hariyati; Melissa Selviany; Herawani Herawani (Indonesian Journal of Global Health Research, 2026)
The daily competency log represents an innovative strategy to enhance nurses’ clinical competency development, particularly in the high-complexity environment of the Neonatal Intensive Care Unit (NICU). This initiative aims to implement and evaluate the daily competency log as a structured tool for monitoring, reflection, and strengthening nursing professionalism at X Hospital. A quality improvement case report approach was applied, encompassing observation, interviews, questionnaires, implementation, and evaluation phases. This study involved 29 NICU nurses selected through total sampling to evaluate the implementation of a Daily Nursing Competency Log. The instrument showed good validity (r > 0.514) and high reliability (Cronbach’s Alpha = 0.87), supporting its effectiveness in improving documentation, reflection, and professional accountability among nurses. Prior to its introduction, no structured competency documentation system existed, not all NICU nurses were certified, and nurse placement was not fully aligned with competency levels. Through pilot testing, socialization, and ongoing mentorship, the daily competency log was successfully introduced and gradually adopted. Digital evaluation indicated that nurses perceived the tool as beneficial for recording daily nursing practices, despite technical limitations such as suboptimal formatting and inefficient competency search features. Conducted collaboratively with the Assistant Manager of Nursing Care, the initiative also established a follow-up plan to refine the system and its content. In conclusion, the daily competency log contributes positively to the advancement of NICU nurses’ clinical competencies and holds significant potential for sustainable integration into the hospital’s nursing human resource quality management system.